Mission Interference: How Competition Confounds Accountability for Environmental Nongovernmental Organizations. Issue 1 (28th November 2016) - Balboa, Cristina M.
Abstract: Kramarz and Park (2016) claim that global environmental governance's increased accountability mechanisms are not matched with environmental gains. I assert that this "accountability paradox" develops for environmental nongovernmental organizations (ENGOs) due to a convergence of trends: ENGOs' increased governance roles coupled with competition for funding and agenda space produces a field riddled with opposing or diverging views. These organizations cannot fully satisfy other actors' demands and achieve "balanced accountability" because of their differentiated and conflicting approaches to environmental problem‐solving. Instead, ENGOs face an accountability dilemma: let the various demands of accountability interfere with their ability to achieve mission or let their missions interfere with their efforts to be accountable. This constrained choice is delineated by Koppell's multiple accountabilities disorder and the new concept "single accountability disorder." The qualitative case of the International Marinelife Alliance demonstrates how an ENGO moves through the multiple accountability states that constitute this paradox.